Intraluminal Thrombus of the Extracranial Cerebral Arteries in Acute Ischemic Stroke: Manifestations, Treatment Strategies, and Outcome - Alhowaish TS; Alhamadh MS; Alsulayhim A; Alotaibi N; Alrashid AA; Alhabeeb AY; Alqirnas MQ; Alrushid E; Alnafisah MS; Anversha AA (Vascular Health and Risk Management, 2024)
Thamer S Alhowaish,1,2 Moustafa S Alhamadh,2,3 Abdullah Alsulayhim,2,4 Najla Alotaibi,5 Azzam Abdulaziz Alrashid,2,3 Abdulrahman Yousef Alhabeeb,2,3 Muhannad Q Alqirnas,2,3 Eythar Alrushid,1,2 Mohammed S Alnafisah,1,2 Ajmal Ali Anversha1,2 1Division of Neurology, Department of Medicine, King Abdulaziz Medical City, Ministry of the National Guard Health Affairs (MNGHA), Riyadh, Kingdom of Saudi Arabia; 2King Abdullah International Medical Research Center, Ministry of the National Guard-Health Affairs, Riyadh, 11481, Kingdom of Saudi Arabia; 3College of Medicine, King Saud Bin Abdulaziz University for Health Sciences (KSAU-HS), Ministry of the National Guard-Health Affairs, Riyadh, 14611, Kingdom of Saudi Arabia; 4Radiology Department, King Abdul Aziz Medical City, Riyadh, Kingdom of Saudi Arabia; 5College of Public Health, Oregon State University, Corvallis, OR, USACorrespondence: Ajmal Ali Anversha, Division of Neurology, King Abdulaziz Medical City, King Abdullah International Medical Research Center, Ministry of the National Guard Health Affairs, Riyadh, Kingdom of Saudi Arabia, Tel +966-11-8011111 Ext: 13460, Email drajmalali@yahoo.comBackground: Intraluminal thrombus (ILT) of the cervical arteries is an uncommon finding that can lead to acute or recurrent ischemic stroke. Currently, antithrombotic therapy in the form of antiplatelet and/or anticoagulation is considered the mainstay of treatment, but evidence of which one has a better outcome is lacking.Methods: A retrospective cohort study included 28 patients diagnosed with acute stroke or transient ischemic attack with ILT of the extracranial arteries from 2013 to 2022. The primary efficacy outcome was assessed as recurrent stroke, and the primary safety outcome was assessed as hemorrhagic complications. Secondary outcomes were assessed as the resolution of thrombi by CT angiography (CTA) and clinical improvement by the Modified Rankin Scale (mRS) and NIH Stroke Scale (NIHSS).Results: Out of 28 patients, more than half (57.1%; n = 16) were males with a mean age of 57.8 ± 9.5 years and an average BMI of 26.9 ± 4.5 kg/m2. As initial treatment, twenty-four patients received anticoagulation and four received antiplatelet agents. Recurrent strokes were found in four patients (14.29%), and all were initially treated with anticoagulation. One patient in the anticoagulation group had a significant retroperitoneal hemorrhage. None of the patients in the antiplatelets group had a recurrent stroke or bleeding event. Initial treatment with antiplatelet agents significantly improved the NIHSS on day 7 (P = 0.017). A significant improvement in NIHSS on day 90 was observed in the anticoagulant group (P = 0.011). In the follow-up CTA performed on 24 patients, 18 (75%) showed complete resolution (3 out of 3 (100%) in the antiplatelet group and 15 out of 21 (71.43%) in the anticoagulant group).Conclusion: Initial treatment with anticoagulants improves neurologic outcomes in patients with ILT-induced acute ischemic stroke but carries the risk of recurrent stroke and bleeding. However, initial treatment with dual antiplatelet agents appears to have comparable efficacy without sequelae, particularly in atherosclerosis-induced ILT.Keywords: stroke, free-floating thrombus, intraluminal thrombus, Intraluminal clot, doughnut sign, antithrombotic, anticoagulation, antiplatelet agents, stroke in Saudi Arabia